Theory based e-mail intervention for promoting cancer prevention through nutrition and lifestyle behaviour change: design of researchprotocol - S. M., Cheong; C. Y., Wong; Kandiah, Mirnalini (Nutrition Society of Malaysia, 2008)
Increasing intake of fruits and vegetables, decreasing fat intake, as well as increasing daily physical activity, are believed to be helpful in preventing cancer and other chronic diseases. Prevalence of physical inactivity and unhealthy diets in the Malaysian population have been reported to be moderately high. Interventions that incorporate effective behaviour-change principles and that can be delivered inexpensively to large segments of the population are urgently needed. The email is a promising mode of delivery for promoting physical activity and nutrition at the workplace. The purpose of this study is to implement and evaluate a 10-week workplace e-mail intervention designed to promote physical activity and healthy nutrition behaviour. This intervention will be carried out at Universiti Putra Malaysia, a campus with over 2000 employees and with state-of-the -art Internet technology. Employees with access to a personal e-mail will be randomly assigned to an intervention or a control group. The intervention group will receive a total of 10 physical activities and 10 nutrition paired messages to their e-mail address between June and August 2008. The control group will not receive any messages during the 10 week study period but the control will be notified that they would receive all the messages at the end of the intervention period. The intervention module will be in the Malay language and will be developed based on the World Cancer Research Fund Dietary Guidelines for Cancer Prevention (WCRF, 2007) and will be implemented by adopting the psychosocial constructs of the Theory of Planned Behaviour. In addition, 5-10 minutes phone call motivational support will be provided after 2-3 weeks of message delivery. Each participant will complete self-report measures of physical activity and nutrition related to knowledge, attitudes, and behaviours at baseline (time 1), 3 months (time 2) and 6 months (time 3) after the intervention.